Interfacial Charge Field in Hierarchical Yolk–Shell Nanocapsule Enables Efficient Immobilization and Catalysis of Polysulfides Conversion. Issue 37 (31st July 2019) - Liu, Handing; Chen, Ziliang; Zhou, Lin; Pei, Ke; Xu, Pingdi; Xin, Linshen; Zeng, Qingwen; Zhang, Jie; Wu, Renbing; Fang, Fang; Che, Renchao; Sun, Dalin
Abstract: Inhibiting the shuttle effect of lithium polysulfides and accelerating their conversion kinetics are crucial for the development of high‐performance lithium–sulfur (Li–S) batteries. Herein, a modified template method is proposed to synthesize the robust yolk–shell sulfur host that is constructed by enveloping dispersive Fe2 O3 nanoparticles within Mn3 O4 nanosheet‐grafted hollow N‐doped porous carbon capsules (Fe2 O3 @N‐PC/Mn3 O4 ‐S). When applied as a cathode for Li–S batteries, the as‐prepared Fe2 O3 @N‐PC/Mn3 O4 ‐S can deliver capacities as high as 1122 mAh g −1 after 200 cycles at 0.5 C and 639 mAh g −1 after 1500 cycles at 10 C, respectively. Remarkably, even as the areal sulfur loading is increased to 5.1 mg cm −2, the cathode can still maintain a high areal specific capacity of 5.08 mAh cm −2 with a fading rate of only 0.076% per cycle over 100 cycles at 0.1 C. By a further combination analysis of electron holography and electron energy loss spectroscopy, the outstanding performance is revealed to be mainly traced to the oxygen‐vacancy‐induced interfacial charge field, which immobilizes and catalyzes the conversion of lithium polysulfides, assuring low polarization, fleet redox reaction kinetics, and sufficient utilization of sulfur. These new findings may shed light on the dependence of electrochemical performance on the heterostructure of sulfur hosts. Abstract : A modified template method is employed to synthesize the robust yolk–shell sulfur host that is constructed by enveloping dispersive Fe2 O3 nanoparticles within Mn3 O4 nanosheet‐grafted hollow N‐doped porous carbon capsules, which generates the oxygen‐vacancy‐induced interfacial charge field, greatly immobilizing and catalyzing the conversion of lithium polysulfides, thus assuring the low polarization, fast redox reaction kinetics, and sufficient utilization of sulfur.